2018
DOI: 10.1111/jfbc.12587
|View full text |Cite
|
Sign up to set email alerts
|

Tiger nut oil-based diet improves the lipid profile and antioxidant status of male Wistar rats

Abstract: The effects of tiger nut oil‐based diet on the lipid profile and activities of cellular enzymes of male rats were investigated. Rats were randomized into two groups and, fed control diet (soya bean oil‐based diet) and tiger nut oil‐based diet for 21 days. Total cholesterol (TC), triglyceride (TG), low‐density lipoprotein cholesterol (LDLc), and very low‐density lipoprotein cholesterol (VLDLc) were significantly lowered in the serum of tiger nut oil‐based diet‐fed rats. Conversely, the high‐density lipoprotein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Consumption of plant‐based foods is on the increase (Ibitoye, Aliyu, & Ajiboye, ) because of awareness of their health benefits and bioactive constituents such as polyphenols and micro‐ and macronutrients (Ibitoye, Olofinsan, et al, ; Oloyede et al, ). In this study, we present gallic and protocatechuic acids as the α‐amylase and α‐glucosidase inhibitory principles in H. sabdariffa calyx.…”
Section: Resultsmentioning
confidence: 99%
“…Consumption of plant‐based foods is on the increase (Ibitoye, Aliyu, & Ajiboye, ) because of awareness of their health benefits and bioactive constituents such as polyphenols and micro‐ and macronutrients (Ibitoye, Olofinsan, et al, ; Oloyede et al, ). In this study, we present gallic and protocatechuic acids as the α‐amylase and α‐glucosidase inhibitory principles in H. sabdariffa calyx.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the capacity of tiger nut to counteract the effect of H 2 O 2 may suggest that the antioxidant capacity, mainly ascribed to its polyphenol and α-tocopherol contents [ 8 ], could also be responsible for the recovery of epithelial barrier function induced by oxidative stress. Along these lines, there have been descriptions of an increase in reduced glutathione in the liver, kidney, and heart among rats fed a diet based on tiger nut oil [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that the mixed oil resulted in a lower serum cholesterol level of rats compared with the control. Ibitoye et al studied the influence of tiger nut oil and soybean oil on the lipid profile of male Wistar rats [ 41 ]. They found that rats fed with tiger nut oil displayed a lower level of the total cholesterol, triglycerides, low-density lipoprotein cholesterol and higher levels in the high-density lipoprotein cholesterol and glutathione compared with that of rats fed with soybean oil.…”
Section: Tiger Nut Oilmentioning
confidence: 99%